Buying and Selling Used Clothing: An Islamic Economy Law Perspective - Wahyu Ziaulhaq (Journal of Nusantara Economy, 2022)
This study aims to describe the buying and selling of used clothing from the perspective of Islamic Economy Law. This type of research is qualitative and normative legal research, namely what we know as library law research, namely legal articles that are carried out by research based on materials sourced from libraries. Sources of data used by the author in this article include primary legal materials, namely applicable laws and regulations that provide descriptions of primary legal materials in the form of interpretations, available books, journals, documents, and other references related to this article. The results of writing this article are as follows: First, buying and selling used clothes can be done if the clothes do not cause negative effects (mudharat) on the buyer's body. Second, buying and selling used clothes can be done if the terms and conditions of buying and selling must be fulfilled. Third, the practice of khiyar (choosing); in this case, if the seller gets a defect at the time of sale and purchase or before the delivery occurs, he is entitled to khiyar, but if in the transaction, both parties know and are mutually willing, then there is no need for khiyar.   Penelitian ini bertujuan untuk mendeskripsikan jual beli pakaian bekas dalam perspektif Hukum Ekonomi Islam. Jenis penelitian ini adalah penelitian kualitatif dan penelitian hukum normative; yang kita kenal dengan penelitian hukum kepustakaan,. Sumber data yang digunakan penulis dalam artikel ini meliputi bahan hukum primer yaitu peraturan perundang-undangan yang berlaku yang memberikan gambaran bahan hukum primer berupa tafsir, buku umum, jurnal, dokumen dan referensi lain yang berkaitan dengan artikel ini. Dari hasil penulisan artikel ini yaitu: Pertama, jual beli pakaian bekas dapat dilakukan apabila pakaian tersebut tidak menimbulkan efek negatif (mudharat) bagi tubuh pembeli. Kedua, jual beli pakaian bekas dapat dilakukan jika syarat dan ketentuan jual beli harus dipenuhi. Ketiga, adanya hak khiyar (memilih), dalam hal ini jika penjual mendapat cacat pada saat jual beli atau sesudahnya, sebelum terjadi penyerahan, ia berhak atas khiyar, tetapi jika dalam transaksi kedua belah pihak mengetahui dan saling rela, maka tidak perlu adanya khiyar.